Highly selective urea electrooxidation coupled with efficient hydrogen evolution - Zhan, Guangming; Hu, Lufa; Li, Hao; Dai, Jie; Zhao, Long; Zheng, Qian; Zou, Xingyue; Shi, Yanbiao; Wang, Jiaxian; Hou, Wei; Yao, Yancai; Zhang, Lizhi (Nature communications, 2024)
Electrochemical urea oxidation offers a sustainable avenue for H 2 production and wastewater denitrification within the water-energy nexus; however, its wide application is limited by detrimental cyanate or nitrite production instead of innocuous N 2 . Herein we demonstrate that atomically isolated asymmetric Ni–O–Ti sites on Ti foam anode achieve a N 2 selectivity of 99%, surpassing the connected symmetric Ni–O–Ni counterparts in documented Ni-based electrocatalysts with N 2 selectivity below 55%, and also deliver a H 2 evolution rate of 22.0 mL h –1 when coupled to a Pt counter cathode under 213 mA cm –2 at 1.40 V RHE . These asymmetric sites, featuring oxygenophilic Ti adjacent to Ni, favor interaction with the carbonyl over amino groups in urea, thus preventing premature resonant C⎓N bond breakage before intramolecular N–N coupling towards N 2 evolution. A prototype device powered by a commercial Si photovoltaic cell is further developed for solar-powered on-site urine processing and decentralized H 2 production. Urea electrooxidation often produces harmful cyanates and nitrites instead of N2, limiting its use in wastewater denitrification. Here, the authors develop an asymmetric Ni–O–Ti catalytic sites on Ti foam that reduce these byproducts, achieve 99% N2 selectivity, and boost H2 evolution.